The Influence of Economic Growth, Human Development Index, and Open Unemployment Rate on Poverty Levels in Sumenep Regency - Ardiyanto Maksimilianus Gai; Monsar Marito Sir; Maria Alvionita Paru; Primus Aryunto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the impact of economic growth, the Human Development Index (HDI), and the open unemployment rate on poverty levels in Sumenep Regency. Using a quantitative approach with multiple regression analysis, this research analyzes secondary data from the Central Bureau of Statistics (BPS) for the period 2015–2023. The results indicate that economic growth significantly reduces poverty by generating employment opportunities and increasing household income. However, HDI does not show a significant effect, suggesting that improvements in health, education, and income require longer-term interventions to impact poverty reduction. Conversely, the open unemployment rate has a significant positive effect on poverty levels, indicating that higher unemployment contributes to increased poverty rates due to reduced purchasing power. Based on these findings, policy recommendations include promoting economic growth through infrastructure development and investment support, enhancing HDI by improving education and healthcare access, and reducing unemployment through job creation programs and vocational training. These integrated strategies are expected to lower poverty rates and enhance overall welfare in Sumenep Regency.